The CFTR Ion Channel: Gating, Regulation, and Anion Permeation - Hwang, Tzyh-Chang (Cold Spring Harbor Laboratory Press, 2013)
Cystic fibrosis transmembrane conductance regulator (CFTR) is an ATP-gated anion channel with two remarkable distinctions. First, it is the only ATP-binding cassette (ABC) transporter that is known to be an ion channel—almost all others function as transport ATPases. Second, CFTR is the only ligand-gated channel that consumes its ligand (ATP) during the gating cycle—a consequence of its enzymatic activity as an ABC transporter. We discuss these special properties of CFTR in the context of its evolutionary history as an ABC transporter. Other topics include the mechanisms by which CFTR gating is regulated by phosphorylation of its unique regulatory domain and our current view of the CFTR permeation pathway (or pore). Understanding these basic operating principles of the CFTR channel is central to defining the mechanisms of action of prospective cystic fibrosis drugs and to the development of new, rational treatment strategies.